BLOOD TRANSFUSION SERVICES IN COVID: SCALING THE UNSCALABLE - CHOWDHRY, MOHIT; ANKITA SHARMA; AGRAWAL, SOMA; MISHRA, MANOJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present manuscript discusses our journey of providing safe BTS during this ongoing COVID-19 pandemic. Methods: It was a single-center, retrospective type of study conducted over a period of 1 year (January 2020–December 2020) in the department of transfusion medicine. The number of donations (replacement and voluntary) was compared during the pre-COVID months with that during the COVID outbreak. The measures included but were not limited to various aspects of staff management, environmental factors, guidelines implementation, and innovative assertions for implementing COVID-19 appropriate behavior. Gradually, provisions were also made for the collection of the COVID convalescent plasma from the recovered donors as a part of the management guidelines issue by the Indian Council of Medical Research. Results: COVID-19 pandemic has had a drastic negative impact on the blood donation but it has also highlighted the potential and the ability of the BTS to withstand such testing times. Conclusion: COVID-19 has left a profound impact on the blood transfusion services. It has highlighted the importance of having a coping strategy in place to withstand such times without compromising the health and the needs of the patients.